A Buddhist Emblem and its Counterpart - Jairazbhoy, R. A. (1963)
surmounting the gatepost of the Buddhist stupa at Sānchī, c. 50 B.C., are pairs of enigmatic symbolical sculptures sometimes described as triśūlas: there is no closer parallel than a bronze statuette from Luristan (A. Godard, Bronzes du Luristan, no. 195).